ANALYSIS OF THE LOCAL BUDGET TO THE LOCAL ECONOMY DEVELOPMENT (Case Study: Malang District) - ROHMAH, ARIFATUR (Jurnal Ilmiah Mahasiswa FEB, 2016)
One of the aspects of the national economic development which is important for the developing countries, such as Indonesia is the issue of the regional development. The regional development is the effort to increase the capacity of local government to manage its economic resources in an effective and efficient manner for the improvement of the area and for the welfare of the people. Generally, the regional development is the development in a certain area which is adjusted to the physical abilities, the socio-economic condition and the applicable rules. Especially in Education, Health, and Infrastructure Sector. Very important to manage the budget for increasing economic development in Malang District with used 3 Sector for better Malang District.Descriptive Qulaitative method by using interview was used to analyzed the local budget to the local economy development as the variable. Result of the research showed that local budget is influence on the local economy development in Malang District with the right act.Keywords:Â  Regional Budget Malang District, Economic Development, Economic Development in Education, Health, Infrastructure in Malang District